Legal Analysis of DPR Authority in Evaluating the Corruption Eradication Commission: A Siyasah Dusturiyah Perspective - Mhd. Naufal Ahnaf; Maulidya Mora Matondang (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the authority of the House of Representatives (DPR) in conducting evaluations of the Corruption Eradication Commission (KPK) as regulated in Article 228A of DPR Regulation Number 1 of 2020, as well as to examine it from the perspective of Siyasah Dusturiyah. This study is motivated by the ongoing debate regarding the limits of legislative authority in exercising oversight over independent state institutions, particularly the KPK which plays a strategic role in combating corruption in Indonesia. This research employs a normative legal research method using a statutory approach and a conceptual approach, which relies on the analysis of legal norms, doctrines, and relevant literature. The results of the study indicate that constitutionally the DPR has an oversight function over the administration of government; However, the implementation of evaluations of the KPK must still consider the principle of institutional independence as specified in the legislation. From the perspective of Siyasah Dusturiyah, oversight of the exercise of power constitutes part of the principle of maintaining justice and preventing the abuse of authority. Nevertheless, its implementation must be based on the values ​​of justice, public benefit (maslahah), and must not create domination of power among state institutions. Therefore, the evaluation mechanism of the KPK should be carried out proportionally so that it remains consistent with the principle of checks and balances within the constitutional system as well as the values ​​of justice within the perspective of Islamic law